Socioeconomic Status Association With Dependency From Objective and Subjective Assessments: A Cross-Sectional Study - Pan, YiYang; Aierken, Ayizuhere; Ding, XiWen; Chen, Yuan; Li, Ying (Frontiers in Psychiatry, 2022)
Background: The effect of socioeconomic status (SES) on dependency is still complex and not fully clear. The purposes of this study are to assess the association between SES and dependency using both objective and subjective assessments. Methods: A cross-sectional study was conducted in 27 locations in China among 1276 general residents aged 60 and above through a complex multistage sampling design. Data were collected using questionnaire survey on-site by well-trained investigators through face-to-face interviews. The dependency was assessed using standardized Chinese version of the Minnesota Multiphasic Personality Inventory-II scale. Objective SES was assessed by the combination of education levels, individual income, pre-retirement occupation and medical insurance. Subjective SES was measured using the MacArthur Scale. The logistic regression analysis was used to evaluate the association between objective SES and dependency. Analysis of covariance was conducted to compare the mean of dependency scores in different levels of SES. Results: Bivariate analysis showed that the levels of objective SES were associated with dependency, depressive, social resources, and region. the logistic regression analysis showed a significant negative association between the levels of objective SES and dependency. The odds ratio was 1.84 (95% confidence interval, 1.07-3.18) after adjusting for important confounding factors. The analysis of covariance showed differences in the mean of dependency scores among different groups defined by different levels of SES. Conclusions: The levels of SES were negatively associated with dependency and subjective SES had a stronger association with dependency than objective SES. The effect of subjective SES on dependency is possibly associated with the perception of position in the social hierarchy.